Recursive deconvolution of combinatorial chemical libraries. - Erb, E (1994)
A recursive strategy that solves for the active members of a chemical library is presented. A pentapeptide library with an alphabet of Gly, Leu, Phe, and Tyr (1024 members) was constructed on a solid support by the method of split synthesis. One member of this library (NH2-Tyr-Gly-Gly-Phe-Leu) is a native binder to a beta-endorphin antibody. A variation of the split synthesis approach is used to build the combinatorial library. In four vials, a member of the library's alphabet is coupled to a solid support. After each coupling, a portion of the resin from each of the four reaction vials was set aside and catalogued. The solid support from each vial is then combined, mixed, and redivided. The steps of (i) coupling, (ii) saving and cataloging, and (iii) randomizing were repeated until a pentapeptide library was obtained. The four pentapeptide libraries where the N-terminal amino acid is defined were screened against the beta-endorphin antibody and quantitated via an ELISA. The amino acid of the four pools that demonstrated the most binding was then coupled to the four tetrapeptide partial libraries that had been set aside and catalogued during the split synthesis. This recursive deconvolution was repeated until the best binders were deduced. Besides the anticipated native binder, two other members of the library displayed significant binding. This recursive method of deconvolution does not use a molecular tag, requires only one split synthesis, and can be applied to the deconvolution of nonlinear small-molecule combinatorial libraries and linear oligomeric combinatorial libraries, since it is based only on the procedure of the synthesis.